Machineries of Oil : An Infrastructural History of BP in Iran - Shafiee, Katayoun (Book collections on Project MUSE., 2018)
This book rethinks the politics of the Middle East through a study of the British-controlled oil industry in Iran between 1901 and 1954. Based on research in governmental and business archives in Iran, the United Kingdom, and the United States, it examines a series of disputes concerning petroleum exploration, property rights, the organization of labor, geological knowledge, accounting methods, oil distribution, and the calculation and control of profits. The goal is to understand how the construction of oil infrastructure reconfigured the local politics of the oil regions and how these arrangements in turn shaped the emergence of both the national state and the multinational oil corporation now known as BP. There has been no study of this kind, with the amount of rich, first-hand information Shafiee has gathered from Iran and elsewhere. Shafiee rethinks the role of oil in the early to mid-twentieth century as a non-human actor whose agency shapes and is shaped by the various techno-social transformations she discusses. She combines archival research with extensive field work at various sites in Iran--sources that are missing from the scholarship on both Iran and the oil industry.